PENGARUH CITRA MEREK, PROMOSI DAN E-WOM TERHADAP KEPUTUSAN PEMBELIAN PRODUK ECOKING DI KOTA BATAM - Kevin; Hikmah, Hikmah (LPPM Universitas Putera Batam, 2025)
Business development in Batam City is rapidly increasing, creating intense competition among companies. In this context, it is crucial for companies to implement effective marketing strategies to attract consumers. This study aims to examine the purchasing decision model of EcoKing products by considering three independent variables: brand image, promotion, and electronic word of mouth (E-WOM). The research method used is quantitative with hypothesis testing. Data was obtained through questionnaires distributed to 204 respondents who are consumers of EcoKing products. The data analysis technique used is multiple linear regression, including validity tests, reliability tests, classical assumption tests, influence tests, and hypothesis testing. The results show that brand image, promotion, and E-WOM, both partially and simultaneously, have a positive and significant effect on purchasing decisions for EcoKing products in Batam City.